Grinding stone rod and grinding method
Patent Information
- Application Number
- CN202380055053.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-27
- Filing Date
- 2023-02-09
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-02-09
AI Technical Summary
Existing grinding stones are difficult to achieve the desired surface roughness and wear resistance during the grinding process, especially in the precision grinding of molds, where there are problems with insufficient grinding force and wear.
A grinding rod containing 80-90% by weight of alumina and 20-10% by weight of silica, with an average mullite crystal particle size of less than 25 nm, is used. The grinding is performed by a flexible design that bends in the axial direction, combined with a vibrating or rotating tool, to suppress the embrittlement and wear of the mullite crystals.
It improves the surface roughness of the workpiece being ground, reduces the wear of the grinding stone, ensures grinding force and wear resistance, and reduces the risk of damage and breakage of the grinding stone.
Smart Images

Figure CN119630510B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to grinding stones. Furthermore, it relates to a grinding method using grinding stones. Background Technology
[0002] Patent Document 1 describes a rod-shaped grinding stone made by impregnating a bundle of inorganic long fiber filaments with resin and then curing it. The grinding stone of the same document is used for grinding molds. The grinding stone has a rectangular or circular cross-section and is flexible enough to bend in a direction intersecting its axis. The bundle of inorganic long fiber filaments extends along the axial direction of the grinding stone, with the cross-section of the bundle of filaments exposed at the front end face of the grinding stone.
[0003] In Patent Document 1, when grinding the surface of a workpiece, the base of the grinding stone is held on a tool holder. The tool holder is connected to the spindle of a machine tool, causing the spindle to rotate and pressing the front end of the grinding stone against the surface of the workpiece. Here, the tool holder converts the spindle's rotation into linear reciprocating motion and rotational motion along the spindle's axis. Therefore, the front end of the grinding stone is intermittently pressed against the workpiece to grind the surface. Alternatively, the front end of the grinding stone contacts the workpiece while rotating to grind the surface.
[0004] Patent Document 2 describes an abrasive for grinding stones. The abrasive in the same document is composed of resin-impregnated inorganic long fibers. The inorganic long fibers contain 80-90% by weight of alumina and 20-10% by weight of silica. The crystal structure of the inorganic long fibers consists of mullite crystals and intermediate alumina. The average grain size of the mullite crystals is 25 nm to 70 nm. In the abrasive of the same document, the inorganic long fibers contain more than 80% by weight of alumina, therefore the inorganic long fibers have high hardness. Furthermore, the average grain size of the mullite crystals is greater than 25 nm, thus resulting in a large grinding force for grinding and polishing workpieces.
[0005] Patent Document 2 describes a cuboid-shaped grinding stone made of the aforementioned abrasive. When grinding a workpiece, the entire side of the grinding stone extending along its long side is pressed against the surface of the workpiece to be ground. Furthermore, the grinding stone is moved back and forth along the surface to be ground.
[0006] Existing technical documents
[0007] Patent documents
[0008] Patent Document 1: Japanese Patent No. 6832555
[0009] Patent Document 2: Japanese Patent Application Publication No. 10-183427 Summary of the Invention
[0010] The technical problem that the invention aims to solve
[0011] If the abrasive for grinding stones described in Patent Document 2 is formed into a rod shape to make a grinding stone rod, the grinding stone rod can have sufficient grinding force. However, with the increasing precision of molds in recent years, the desired surface roughness cannot always be achieved by grinding with a grinding stone rod made of the abrasive for grinding stones described in Patent Document 2. In addition, after dedicated research, the inventors found that there is still room for improvement in the wear resistance of the grinding stone rod made of the abrasive for grinding stones described in Patent Document 2.
[0012] The technical problem to be solved by the present invention is to provide a grinding stone rod capable of improving the surface roughness and wear resistance of the grinding surface of a workpiece. Furthermore, a grinding method using such a grinding stone rod is also intended to be provided.
[0013] Technical solutions adopted to solve technical problems
[0014] The inventors discovered through dedicated research that when the grinding rod is made of inorganic long fibers containing 80-90% alumina and 20-10% silica, and the crystal structure of the inorganic long fibers contains intermediate alumina and mullite, the larger the mullite crystal grains in the crystal structure, the easier it is for scratches (grinding marks) to be generated on the grinding surface of the workpiece.
[0015] Furthermore, the inventors, through dedicated research, discovered that when the grinding rod employs an abrasive in which the inorganic long fibers contain 80-90% by weight alumina and 20-10% by weight silica, and the crystal structure of the inorganic long fibers contains intermediate alumina and mullite, the larger the mullite crystal grains in the crystal structure, the greater the impact on the wear resistance of the grinding rod. That is, mullitization occurs in the inorganic long fibers with large grains. As mullitization proceeds, the inorganic long fibers become brittle. Here, when using a rod-shaped grinding rod containing inorganic long fibers to grind the surface of a workpiece, the front end of the grinding rod is pressed against the surface. Additionally, since the rod-shaped grinding rod has elasticity that bends in the direction intersecting the axis, when the front end is pressed against the workpiece, the grinding rod bounces or vibrates less on the surface, and the possibility of breakage or fracture is also low. Therefore, when pressing the front end of the grinding stone rod against the surface of the object being ground, a relatively large pressing force should be applied, taking into account its elasticity, to ensure the desired grinding force. Consequently, the front end of the grinding stone rod is easily subjected to load, and if the inorganic long fibers exposed on the front end undergo mullite formation, the inorganic long fibers will become brittle and break easily, leading to wear.
[0016] On the other hand, the inventors have discovered that when the grinding wheel uses an abrasive in which the inorganic long fibers contain 80-90% alumina and 20-10% silica by weight, the grinding force of the grinding wheel can be ensured even if the mullite crystals are smaller than 25 nm. That is, if the inorganic long fibers contain more than 80% alumina, the hardness of the grinding wheel can be ensured. In addition, if the mullite crystals are smaller than 25 nm, mullite formation in the inorganic long fibers is suppressed, and thus the embrittlement of the inorganic long fibers is suppressed. As a result, when the front end of the grinding wheel is pressed against the workpiece to grind the surface to be ground, the embrittlement and breakage of the inorganic long fibers are suppressed, and the inorganic long fibers are embedded in the workpiece. Furthermore, when grinding and polishing the workpiece with a rod-shaped grinding wheel, unlike the case of grinding the workpiece by having the entire side extending along the long side in contact with the surface to be ground as in the case of a cuboid-shaped grinding wheel, the front end can be pressed against the surface to be ground with a pressing force that takes into account the elasticity of the grinding wheel. Therefore, the grinding stone can have a specified grinding force. This invention is based on these findings.
[0017] To solve the above-mentioned technical problems, the present invention is characterized by a rod-shaped grinding stone rod, the front end of which is pressed against the grinding surface of a workpiece to grind the grinding surface. The grinding stone rod has multiple inorganic long fibers extending along the axial direction and resin impregnated and cured in the inorganic long fibers. The cross-section of the inorganic long fibers is exposed at the front end face, and it has elasticity to bend in a direction intersecting the axial direction. The inorganic long fibers have 80-90% by weight of alumina and 20-10% by weight of silicon dioxide. The average particle size of the mullite crystals is less than 25 nm. In the diffraction pattern obtained by irradiating the inorganic long fibers with X-rays, the peak value of the diffraction line of the (110) plane of mullite appears. The average particle size of the mullite crystals is calculated based on the diffraction pattern using the following mathematical formula.
[0018]
Mathematical Formula 1
[0019]
[0020] D hkl (210) Average particle size
[0021] λ: Wavelength of X-rays
[0022] θ: Grazing angle of X-rays
[0023] β 1 / 2 The half-width of the diffraction lines on the (210) plane of mullite, which appears near 26° in the crystal structure 2θ, based on X-ray diffraction.
[0024] In the grinding stone rod of the present invention, the average grain size of the mullite crystals in the inorganic long fiber crystal structure is less than 25 nm. This suppresses scratches (grinding marks) on the grinding surface of the workpiece due to the size of the mullite crystals. Therefore, the surface roughness of the grinding surface can be improved. Furthermore, in the grinding stone rod of the present invention, the average grain size of the mullite crystals in the inorganic long fiber crystal structure is less than 25 nm. This suppresses the embrittlement of the inorganic long fibers. Therefore, when the front end of the grinding stone rod, with its front end exposed to reveal the inorganic long fibers, is pressed against the grinding surface of the workpiece for grinding, the embrittlement and breakage of the inorganic long fibers can be suppressed. Therefore, the wear resistance of the grinding stone rod is improved.
[0025] On the other hand, inorganic long fibers contain more than 80% alumina by weight, thus ensuring their hardness. Furthermore, smaller mullite crystals suppress the embrittlement of the inorganic long fibers. Therefore, when grinding with the tip of the grinding stone pressed against the surface of the workpiece, the embrittlement and breakage of the inorganic long fibers are prevented, and the fibers are prevented from becoming embedded in the workpiece. Moreover, when grinding or polishing a workpiece with a rod-shaped grinding stone, unlike grinding with a cuboid-shaped grinding stone where the entire side extending along the long side contacts the surface to be ground, the tip can be pressed against the surface to be ground. Furthermore, since the rod-shaped grinding stone has the elasticity to bend in the direction intersecting its axis, even when the tip is pressed against the surface to be ground, there is less bouncing or vibration of the grinding stone on the surface, and the possibility of breakage or fracture is low. Therefore, the desired grinding force can be obtained by pressing the tip of the grinding stone against the surface to be ground with a pressing force that takes into account the elasticity of the grinding stone. Therefore, even if the average grain size of the mullite crystals is below 25nm, the grinding rod can still ensure its grinding force.
[0026] In this invention, the average grain size of the mullite crystals is preferably below 20 nm. This readily improves the surface roughness of the surface to be polished. Furthermore, it further enhances the wear resistance of the polishing rod.
[0027] In this invention, the alumina content of the aforementioned inorganic long fibers is preferably 85% by weight or more. In this case, it is easier to further increase the hardness of the inorganic long fibers. Therefore, it is easier to ensure the grinding force of the grinding stone.
[0028] In this invention, the resin mentioned above can be an epoxy resin.
[0029] In this invention, the bending strength can be above 500 MPa and the bending elastic modulus above 50 GPa. In this case, the pressure of the front end of the grinding stone pressing against the surface of the object being ground can be increased, making it easier to obtain the desired grinding force.
[0030] Secondly, the grinding method of the present invention is characterized in that the aforementioned grinding stone is mounted on a vibrating tool, and the front end of the aforementioned grinding stone is pressed against the grinding surface of the workpiece while vibrating it along the aforementioned axial direction. The grinding method performed while pressing the front end of the grinding stone against the grinding surface of the workpiece includes a grinding method performed while pressing the front end face of the grinding stone against the grinding surface of the workpiece.
[0031] Furthermore, the grinding method of the present invention is characterized in that the aforementioned grinding stone is mounted on a vibrating tool, and while pressing the front end of the aforementioned grinding stone onto the grinding surface of the workpiece, it is vibrated along the aforementioned axial direction and in the direction intersecting with the axis of the aforementioned grinding stone. The grinding method performed while pressing the front end of the grinding stone onto the grinding surface of the workpiece includes a grinding method performed while pressing the front end face of the grinding stone onto the grinding surface of the workpiece.
[0032] Furthermore, the grinding method of the present invention is characterized in that the aforementioned grinding stone is mounted on a rotating tool, and the front end of the grinding stone is rotated while being pressed against the grinding surface of the workpiece, wherein the cross-section of the grinding stone is circular. The grinding method performed while pressing the front end of the grinding stone against the grinding surface of the workpiece includes a grinding method performed while pressing the front end face of the grinding stone against the grinding surface of the workpiece. Attached Figure Description
[0033] Figure 1 This is the front view of the whetstone.
[0034] Figure 2 Is using Figure 1 A diagram illustrating the grinding method of a workpiece using a grinding stone rod.
[0035] Figure 3 Is using Figure 1 Another illustration of a grinding method for a workpiece using a grinding stone rod.
[0036] Figure 4 This is the front view of a cylindrical grinding stone rod.
[0037] Figure 5 Is using Figure 4 A diagram illustrating the grinding method of a workpiece using a grinding stone rod.
[0038] Figure 6 Is using Figure 4 Another illustration of a grinding method for a workpiece using a grinding stone rod.
[0039] Figure 7 This is a flowchart of the manufacturing process for grinding stones.
[0040] Figure 8This is a diffraction pattern obtained by irradiating the inorganic long fiber of Example 1 with X-rays.
[0041] Figure 9 This is a diffraction pattern obtained by irradiating the inorganic long fiber of Comparative Example 1 with X-rays.
[0042] Figure 10 It is the roughness curve of the grinding surface of the workpiece after grinding by the grinding stone rod of Example 1.
[0043] Figure 11 It is the roughness curve of the grinding surface of the workpiece after grinding with the grinding stone rod of Comparative Example 1.
[0044] Figure 12 This is a graph showing the amount of grinding on the workpiece after the comparative test.
[0045] Figure 13 This is a chart showing the wear of the grinding stone rods after the comparative test.
[0046] Figure 14 This is a diffraction pattern obtained by irradiating the inorganic long fiber of Example 2 with X-rays.
[0047] Figure 15 This is a diffraction pattern obtained by irradiating the inorganic long fiber of the reference example with X-rays.
[0048] Figure 16 This is a diffraction pattern obtained by irradiating the inorganic long fiber of Comparative Example 2 with X-rays.
[0049] Figure 17 It is the roughness curve of the grinding surface of the workpiece after grinding by the grinding stone rod of Example 2.
[0050] Figure 18 It is the surface roughness curve of the workpiece after grinding with a grinding stone rod as an example.
[0051] Figure 19 It is the roughness curve of the grinding surface of the workpiece after grinding with the grinding stone rod of Comparative Example 2.
[0052] Figure 20 This is a graph showing the amount of grinding on the workpiece after the comparative test.
[0053] Figure 21 This is a chart showing the wear of the grinding stone rods after the comparative test. Detailed Implementation
[0054] Hereinafter, the grinding stone rod according to an embodiment of the present invention will be described with reference to the accompanying drawings.
[0055] (Whetstone)
[0056] Figure 1This is the front view of the whetstone. Figure 2 Is using Figure 1 A diagram illustrating the grinding method of a workpiece using a grinding stone rod. Figure 3 Is using Figure 1 Another illustration of a grinding method for a workpiece using a grinding stone rod. Figure 4 This is the front view of a cylindrical grinding stone rod. Figure 5 Is using Figure 4 A diagram illustrating the grinding method of a workpiece using a grinding stone rod. Figure 6 Is using Figure 4 Another illustration of a grinding method for a workpiece using a grinding stone rod.
[0057] like Figure 1 As shown, the grinding stone rod 10 is rod-shaped with a rectangular cross-section. In this example, the grinding stone rod 10 has a rectangular cross-section. The grinding stone rod 10 has multiple inorganic long fibers 15 extending along its axis L and resin 16 impregnated and cured in the inorganic long fibers 15. The inorganic long fibers 15 are polycrystalline fibers with 80-90% by weight alumina content and 20-10% by weight silica content. The cross-section of the inorganic long fibers 15 is exposed at the front end face 17a of the grinding stone rod 10.
[0058] The grinding stone rod 10 has elasticity when bending in a direction intersecting its axis L. The bending strength of the grinding stone rod 10 is 500 MPa or more. The flexural modulus of elasticity of the grinding stone rod 10 is 50 GPa or more. More preferably, the bending strength of the grinding stone rod 10 is 800 MPa or more, and the flexural modulus of elasticity of the grinding stone rod 10 is 65 GPa or more. Furthermore, in... Figure 1 In the accompanying drawings, for convenience, the inorganic long fibers 15 are represented by dashed lines, but the inorganic long fibers 15 extend continuously from the front end of the grinding rod 10 to the base end. In addition, multiple inorganic long fibers 15 are sometimes tilted relative to the axis L of the grinding rod 10, but the tilt angle in this case is about 10° and does not exceed 20°.
[0059] (Grinding method)
[0060] like Figure 2 As shown, the grinding stone 10 is used by mounting its base portion onto the head of a handheld vibratory tool. The vibratory tool is, for example, a pneumatic vibratory tool or an ultrasonic vibratory tool. The vibratory tool causes the grinding stone 10 mounted on the head to reciprocate (vibrate) along its axial direction. The workpiece W that the grinding stone 10 grinds is, for example, a mold used for resin molding.
[0061] When grinding workpiece W, the front end 17 of the grinding stone 10 is pressed obliquely against the grinding surface S of workpiece W. That is, the grinding stone 10 is pressed against the grinding surface S with its axis L forming an acute angle θ with the grinding surface S. In this example, one long side of the rectangular cross-section of the grinding stone 10 is opposite to the grinding surface S. Furthermore, when grinding workpiece W, the grinding stone 10 is pressed against the grinding surface S of workpiece W with a predetermined pressing force F along the axis L. Furthermore, the grinding stone 10... Figure 2 As indicated by the arrow, the grinding stone 10 vibrates along the axial direction when grinding the workpiece W. When the vibrating tool 11 is a pneumatic vibrating tool, it vibrates the grinding stone 10 at a speed of 5000 st / min or higher. When the vibrating tool 11 is an ultrasonic vibrating tool, it vibrates the grinding stone 10 at a frequency of 15 kHz or higher.
[0062] Additionally, 10 whetstones Figure 3 As shown, sometimes its front end face 17a is pressed against the grinding surface S of the workpiece W from the vertical direction to grind the workpiece W. In this case, the grinding stone rod 10 is also pressed against the grinding surface S with a pressing force F from the direction along the axis L. Furthermore, as... Figure 3 As indicated by the solid arrow in the diagram, the grinding stone rod 10 is vibrated along its axial direction by the vibrating tool 11. When the vibrating tool 11 is a pneumatic vibrating tool, it vibrates the grinding stone rod 10 at a speed of 5000 st / min or higher. When the vibrating tool 11 is an ultrasonic vibrating tool, it vibrates the grinding stone rod 10 at a frequency of 15 kHz or higher.
[0063] Here, as Figure 3 As indicated by the solid and dashed arrows, when using a pneumatic vibrating tool, the grinding stone 10 is sometimes vibrated along the axial direction and in a direction orthogonal to the axis L. In this case, the pneumatic vibrating tool achieves vibration along the axial direction and in a direction orthogonal to the axis L by causing the grinding stone 10 to oscillate along an elliptical track during the stroke of the tool that vibrates it along the axial direction. In this case, the pneumatic vibrating tool vibrates the grinding stone 10 at a speed of 5000 s / min or higher.
[0064] Additionally, when using pneumatic vibration tools, such as Figure 2 As shown, when the front end 17 of the grinding stone 10 is pressed against the surface S of the grinding object from an oblique direction to grind the workpiece W, the grinding stone 10 is sometimes also vibrated along the axial direction and in a direction orthogonal to the axis L.
[0065] In addition, such as Figure 5As shown, the whetstone 10 is sometimes used by mounting its base portion onto the head of a handheld rotary tool 11'. In this case, the whetstone mounted on the rotary tool 11' is preferably as follows: Figure 4 The cross-section shown is a circular whetstone rod 10'. That is, preferably, a cylindrical whetstone rod 10' is mounted on a rotary tool 11'. The rotary tool 11' is, for example, an electric rotary tool or a pneumatic rotary tool. Figure 5 As indicated by the solid arrow in the image, the rotating tool 11' causes the grinding stone rod 10' to rotate about its axis.
[0066] like Figure 5 As shown, when grinding workpiece W, the front end 17 of the grinding stone 10' is pressed against the grinding surface S of workpiece W from an oblique angle. That is, the grinding stone 10' is pressed against the grinding surface S with its axis L forming an acute angle θ with the grinding surface S. Furthermore, when grinding workpiece W, the grinding stone 10' is pressed against the grinding surface S of workpiece W with a predetermined pressing force F along the axis L. Then, the grinding stone 10' is rotated about its axis while its front end 17 is pressed against the grinding surface S. The rotating tool 11' rotates the grinding stone 10 at a speed of 100 rpm or more.
[0067] Here, when grinding is performed by mounting the grinding stone 10' on the rotating tool 11', such as Figure 6 As shown, sometimes the front end face 17a of the grinding stone 10' is pressed vertically onto the grinding surface S of the workpiece W, causing it to rotate. In this case, the grinding stone 10' is also pressed onto the grinding surface S with a pressing force F along the axis L. Furthermore, the rotating tool 11' rotates the grinding stone 10 at a speed of 100 rpm or more.
[0068] Here, in any of the above-mentioned grinding methods, when grinding the grinding surface S of the workpiece by means of the grinding stone 10, the grinding stone 10 may sometimes bend in the direction intersecting its axis L due to the pressing force F of pressing the grinding stone 10 on the grinding surface S or the reaction force from one side of the grinding surface S.
[0069] Alternatively, the grinding stones 10 and 10' can be used without being mounted on a vibrating tool or similar device. In this case, the operator presses the front end 17 of the grinding stones 10 and 10' onto the grinding surface S of the workpiece W for manual grinding.
[0070] (Method for manufacturing whetstone rods)
[0071] Figure 7 This is a flowchart of the manufacturing process for grinding stones. (Example:) Figure 7As shown, the manufacturing method of the grinding stone rod 10 sequentially includes a spinning step ST1, a pre-firing step ST2, a sintering step ST3, and a resin impregnation molding step ST4. In the spinning step ST1, an aqueous spinning solution composed of basic aluminum chloride, colloidal silica, and polyvinyl alcohol is dry-spun to obtain precursor fibers. In the pre-firing step ST2, the precursor fibers are sintered at a temperature above 900°C and below 1300°C to form ceramics, obtaining inorganic long fibers. In the sintering step ST3, the inorganic long fibers are heated at a high temperature above 1300°C for approximately 20 seconds. The heating temperature in the sintering step ST3 is higher than the heating temperature in the pre-firing step ST2.
[0072] In the resin impregnation molding process ST4, inorganic long fibers are appropriately aligned to form bundled filaments. Furthermore, in the resin impregnation molding process ST4, the bundled filaments are impregnated with a thermosetting resin such as epoxy resin or phenolic resin. Next, in the resin impregnation molding process ST4, the resin-impregnated bundled filaments are aligned to form a bundle of bundled filaments. Then, in the resin impregnation molding process ST4, the bundle of resin-impregnated bundled filaments is drawn through a mold with an opening of a predetermined shape, and then cured in a heating furnace. Finally, the resin-cured bundle of bundled filaments is cut to a predetermined length. Thus, a grinding stone rod 10 with a predetermined length and a predetermined cross-sectional shape is obtained.
[0073] The following is a specific example of the manufacturing method. First, in the spinning step ST1, 2.5 kg of partially saponified polyvinyl alcohol with an average degree of polymerization of 1700 is dissolved in 34 kg of an alkaline aluminum chloride aqueous solution containing 13.2 wt% aluminum ions and 11.45 wt% chloride ions, and 7.5 kg of colloidal silica containing 20 wt% silica, to prepare a spinning solution with a viscosity of approximately 1000 poise / 20°C. Next, the spinning solution is extruded from a 1000-hole spinning nozzle for dry spinning. In the pre-firing step ST2, the spun inorganic long fibers are fired at 900°C to 1300°C to form ceramic, obtaining bundled yarn. Then, in the sintering step ST3, the bundled yarn is continuously wound onto a first bobbin under tension in a tube furnace at 1300°C to 1400°C. At this time, the throughput of the bundled yarn is adjusted to a heating time of 20 seconds. Here, the bundled filaments are wound around multiple first bobbins.
[0074] In the resin impregnation molding process ST4, bundled filaments are drawn from multiple first tubes and passed through a resin tank containing uncured resin. The resin-impregnated bundled filaments are then pulled together and passed through a heating furnace.
[0075] The resin impregnated in the bundled filaments and the bundle of bundled filaments may have the following composition.
[0076] Epoxy resin (JER828, manufactured by Mitsubishi Chemical Corporation) 100 parts by weight
[0077] Tetrahydromethylphthalic anhydride (HN2200, manufactured by Hitachi Chemical Co., Ltd.) 85 parts by weight
[0078] Imidazole (2E4MZ-CN, manufactured by Shikoku Kasei Corporation) 2 parts by weight
[0079] Here, in the resin impregnation molding process ST4, the bundle of resin-impregnated filaments passes through a mold with an opening of a predetermined shape before reaching the heating furnace. This causes the cross-sectional shape of the resin-impregnated filament bundle to correspond to the shape of the mold opening. Furthermore, in the resin impregnation molding process ST4, the impregnated resin is cured by passing through the heating furnace. Therefore, the cured filament bundle is cut to a predetermined size. Thus, when the mold opening is rectangular, a grinding stone rod with a predetermined length and rectangular cross-section can be obtained. When the mold opening is circular, a grinding stone rod with a predetermined length and circular cross-section can be obtained.
[0080] (Example 1)
[0081] The grinding stone rod 10 in Example 1 is rod-shaped, with a rectangular cross-section orthogonal to the axis L. The grinding stone rod 10 has a thickness (dimension along the shorter side of the cross-section) of 1 mm, a width (dimension along the longer side of the cross-section) of 4 mm, and a length of 100 mm. The grinding stone rod 10 has a bending strength of 1200 MPa and a bending modulus of elasticity of 115 GPa.
[0082] The grinding stone rod 10 has multiple inorganic long fibers 15 extending along its axial direction and resin 16 impregnated in the inorganic long fibers 15. The inorganic long fibers 15 have an alumina content of 85% by weight and a silica content of 15% by weight. The crystal structure of the inorganic long fibers 15 has mullite crystals and intermediate alumina. The average particle size of the mullite crystals is 20 nm. The cross-section of the inorganic long fibers 15 is exposed at the front end face 17a of the grinding stone rod 10.
[0083] In manufacturing the grinding stone rod 10 of Example 1, the heating temperature of the pre-firing process ST2 is 1000°C. The heating temperature of the sintering process ST3 is 1380°C. The heating time in the sintering process ST3 is 20 seconds.
[0084] Here, the crystal structure of the inorganic long fiber 15 is evaluated using X-ray diffraction. That is, after the sintering process ST3 and before the resin impregnation molding process ST4, the inorganic long fiber 15 is irradiated with X-rays to obtain a diffraction pattern. Figure 8This is a diffraction pattern of the inorganic long fiber 15 from Example 1 when irradiated with X-rays. Furthermore, based on the diffraction pattern, the average grain size of the mullite crystals was calculated using the following general formula.
[0085]
Mathematical Formula 1
[0086]
[0087] D hkl (210) Average particle size
[0088] λ: Wavelength of X-rays
[0089] θ: Grazing angle of X-rays
[0090] β 1 / 2 The half-width of the diffraction lines on the (210) plane of mullite, which appears near 26° in the crystal structure 2θ, based on X-ray diffraction.
[0091] Figure 8 The average grain size of the mullite crystals of the inorganic long fiber 15 obtained from the diffraction pattern shown is Dhkl = 20 (nm).
[0092] Furthermore, the peak value of the diffraction lines on the (210) plane of mullite decreases as the grain size of the mullite crystal decreases, and sometimes it is obscured by other diffraction lines. For example, when the grain size of the mullite crystal is less than 25 nm, the peak value of the diffraction lines on the (210) plane of mullite is sometimes obscured by other diffraction lines, making it impossible to obtain the half-width of the diffraction lines. In response to this, the inventors, through experiments, confirmed that the average grain size of the mullite crystal is less than 20 nm when the peak value of the diffraction lines on the (210) plane of mullite is obscured by other diffraction lines and the half-width of the diffraction lines cannot be obtained, using other measurement methods. In addition, even when the peak value of the diffraction lines on the (210) plane of mullite is obscured by other diffraction lines, as long as the peak value of the diffraction lines on the (110) plane of mullite appears in the diffraction pattern, it can be determined that the crystal structure of the inorganic long fiber 15 contains mullite crystals.
[0093] (Comparative Example)
[0094] The grinding stone rod of Comparative Example 1 is rod-shaped with a rectangular cross-section orthogonal to the axis. The grinding stone rod 10 has a thickness (dimension along the shorter side of the cross-section) of 1 mm, a width (dimension along the longer side of the cross-section) of 4 mm, and a length of 100 mm. The grinding stone rod has a flexural strength of 1200 MPa and a flexural modulus of 120 GPa. The grinding stone rod of Comparative Example 1 comprises multiple inorganic long fibers extending along the axial direction and resin impregnated within the inorganic long fibers. The inorganic long fibers contain 85% by weight of alumina and 15% by weight of silica. The crystal structure of the inorganic long fibers consists of mullite crystals and intermediate alumina. The cross-section of the inorganic long fibers is exposed at the front end face of the grinding stone rod of Comparative Example 1.
[0095] Figure 9 This is the diffraction pattern of the inorganic long fiber of Comparative Example 1 when irradiated with X-rays. Figure 9 The diffraction pattern shown clearly reveals the peak value of the diffraction lines from the (210) plane of mullite. Based on Figure 9 The diffraction pattern shown indicates that the average grain size of the mullite crystals from the inorganic long fibers of Comparative Example 1 is Dhkl = 35 (nm). That is, the average grain size of the mullite crystal particles is greater than 25 nm.
[0096] In manufacturing the grinding stone rod of Comparative Example 1, the heating temperature of the pre-firing process ST2 was 1000°C. The heating temperature of the sintering process ST3 was 1390°C. The heating time in the sintering process ST3 was 30 seconds.
[0097] Compared to the heating temperature of sintering step ST3 in Example 1, the heating temperature of sintering step ST3 in Comparative Example 1 is higher. The heating time of sintering step ST3 in Comparative Example 1 is also longer than that of sintering step ST3 in Example 1. Therefore, the grinding wheel of Comparative Example 1 has mullite crystals with an average particle size of 25 nm or more in its crystal structure. Thus, by controlling the heating temperature and heating time of the sintering step ST3 during the manufacture of the grinding wheel, the average particle size of the mullite crystals in the crystal structure of the inorganic long fiber can be controlled.
[0098] (Comparative Test)
[0099] A comparative test was conducted on grinding workpiece W using the grinding stone rod 10 of Example 1 and the grinding stone rod of Comparative Example 1. Figure 10 It is the roughness curve of the grinding surface of the workpiece after grinding with the grinding stone rod of Example 1. Figure 11 It is the surface roughness curve of the workpiece after grinding with the grinding stone rod of Comparative Example 1. Figure 12 This is a graph showing the amount of grinding material removed from the workpiece after a comparative test in which the workpiece was ground using the grinding stone rods of Example 1 and Comparative Example 1. Figure 13This is a graph showing the wear of the grinding stone rods after a comparative test was conducted using the grinding stone rods of Example 1 and Comparative Example 1 to grind workpieces.
[0100] In the comparative test, the base of the grinding stone 10 was mounted on the head of a handheld vibratory tool 11, and the grinding surface S of the workpiece W was ground. The vibratory tool was a pneumatic vibratory tool. The workpiece W being ground was a mold. The material of the workpiece W was S50C (carbon steel for mechanical structures).
[0101] More specifically, such as Figure 2 As shown, during the grinding of workpiece W, the grinding stone 10 of Example 1 and the grinding stone 1 of Comparative Example 1 were positioned such that the angle θ between their axis L and the grinding target surface S was 30°. Furthermore, the front end 17 of the grinding stone 10 of Example 1 and the front end of the grinding stone 1 of Comparative Example 1 were pressed against the grinding target surface S with a pressing force F of 6 N. Then, the grinding stone 10 of Example 1 and the grinding stone 1 of Comparative Example 1 were vibrated along the axial direction at 21000 st / min using a vibration tool 11. Finally, the workpiece W was continuously subjected to dry grinding for 3 minutes with a grinding area of 30 mm × 30 mm.
[0102] from Figure 12 As can be seen from the graph of grinding amount of the workpieces after the comparative test, the grinding stone 10 of Example 1 is considered to have the same grinding force as the grinding stone 1 of Comparative Example 1.
[0103] in addition, Figure 10 The scratches produced in the roughness curve of the workpiece surface after grinding with the grinding stone rod 10 of Example 1 are shown to be greater than those produced in Example 1. Figure 11 The roughness curve of the workpiece surface after grinding with the whetstone of Comparative Example 1 shows fewer scratches. Furthermore, the surface roughness of the workpiece W's surface S after grinding with the whetstone 10 of Example 1 is Rz 2.0 μm. The surface roughness of the workpiece W's surface S after grinding with the whetstone of Comparative Example 1 is Rz 4.1 μm. Therefore, when grinding with the whetstone 10 of Example 1, the surface roughness of the workpiece W's surface S can be improved.
[0104] Furthermore, from Figure 13 As shown in the graph of wear amount of the grinding stone rods after the comparative test, the wear amount of the grinding stone rod 10 of Example 1 is less than that of the grinding stone rod of Comparative Example 1. Therefore, the wear resistance of the grinding stone rod 10 of Example 1 is improved compared with that of the grinding stone rod of Comparative Example 1.
[0105] (Effects)
[0106] In the grinding stone 10 of this example, the average grain size of the mullite crystals in the crystal structure of the inorganic long fiber 15 is less than 25 nm. This suppresses scratches (grinding marks) on the surface of the workpiece due to the size of the mullite crystals. Therefore, the surface roughness of the surface being ground can be improved.
[0107] Furthermore, in the grinding stone 10 of this example, the average grain size of the mullite crystals in the crystal structure of the inorganic long fibers 15 is less than 25 nm. This suppresses the embrittlement of the inorganic long fibers 15, thus preventing the inorganic long fibers 15 from becoming brittle and breaking during grinding by pressing the front end 17 of the grinding stone 10 onto the grinding surface S of the workpiece W. Therefore, the wear resistance of the grinding stone 10 is improved.
[0108] On the other hand, the inorganic long fibers 15 have an alumina content of 80% or more by weight, thus ensuring their hardness. Furthermore, if the mullite crystals are small, the embrittlement of the inorganic long fibers 15 can be suppressed. Therefore, when grinding by pressing the tip 17 of the grinding rod 10 against the grinding surface S of the workpiece W, the embrittlement and breakage of the inorganic long fibers 15 can be suppressed, and the inorganic long fibers 15 can be embedded into the workpiece W. Moreover, unlike cuboid grinding stones that grind by contacting the entire side surface with the grinding surface of the workpiece W, the grinding rod 10 grinds by pressing the tip 17 against the grinding surface of the workpiece W. Furthermore, since the grinding rod 10 has elasticity that bends in the direction intersecting its axis L, the tip 17 of the grinding rod 10 can be pressed against the grinding surface with a pressing force F that takes into account the elasticity of the grinding rod 10. Therefore, the grinding rod 10 of Example 1 can ensure grinding force even if the average grain size of the mullite crystals is less than 25 nm.
[0109] Here, through the inventors' experiments, it was confirmed that in the crystal structure of inorganic long fibers 15, the smaller the average grain size of mullite crystals, the higher the wear resistance of the grinding rod 10.
[0110] Furthermore, when the inorganic long fibers 15 have an alumina content of 85% or more, the hardness of the inorganic long fibers 15 can be increased compared to when the alumina content is less than 85% by weight. Therefore, in order to ensure the grinding power of the grinding rod 10, it is preferable to have an alumina content of 85% or more. In addition, when the alumina content is 85% or more, the silica content is less than 15% by weight.
[0111] In addition to aluminum oxide and silicon dioxide, the inorganic long fibers 15 sometimes contain other components. In this case, as long as the inorganic long fibers 15 have 80 to 90% by weight of aluminum oxide and 20 to 10% by weight of silicon dioxide, the grinding force of the grinding stone rod 10 can be ensured.
[0112] (Example 2, Reference Example, Comparative Example 2)
[0113] Next, the grinding stone rods 10 of Example 2, Reference Example, and Comparative Example 2 will be described. The grinding stone rods 10 of Example 2, Reference Example, and Comparative Example 2, like the grinding stone rod 10 of Example 1, have multiple inorganic long fibers 15 extending along the axial direction and resin 16 impregnated in the inorganic long fibers 15. The inorganic long fibers 15 have 85% by weight of alumina and 15% by weight of silica. The crystal structure of the inorganic long fibers 15 has mullite crystals and intermediate alumina. The cross-section of the inorganic long fibers 15 is exposed at the front end face 17a of the grinding stone rods 10 of Example 2 and Reference Example.
[0114] Furthermore, the grinding stones of Example 2, Reference Example, and Comparative Example 2 have the same shape as the grinding stone 10 of Example 1. That is, the grinding stone 10 of Example 2, Reference Example, and Comparative Example 2 is rod-shaped, and the cross-sectional shape orthogonal to the axis L is rectangular. Each grinding stone 10 has a thickness of 1 mm, a width of 4 mm, and a length of 100 mm.
[0115] In Example 2, Reference Example 2, and Comparative Example 2, the crystal structure of the inorganic long fiber 15 was evaluated by X-ray diffraction in the same manner as in Example 1. That is, after the sintering process ST3 and before the resin impregnation molding process ST4, the inorganic long fiber 15 was irradiated with X-rays to obtain a diffraction pattern. Figure 14 This is a diffraction pattern of the inorganic long fiber 15 from Example 2 when irradiated with X-rays. Figure 15 This is a diffraction pattern of the inorganic long fiber 15 of the reference example when irradiated with X-rays. Figure 16 This is the diffraction pattern of the inorganic long fiber 15 of Comparative Example 2 when irradiated with X-rays. Similar to the case of Example 1, the average grain size of the mullite crystals was calculated using a general formula based on the diffraction pattern.
[0116] from Figure 14 The diffraction pattern of Example 2 shows that the average grain size of the mullite crystals of the inorganic long fiber 15 is Dhkl = 10 (nm). That is, the average grain size of the mullite crystals of the inorganic long fiber 15 in Example 2 is 10 nm. Here, the flexural strength of the grinding rod 10 of Example 2 is 1200 MPa, and the flexural modulus is 112 GPa. In manufacturing the grinding rod 10 of Example 2, the heating temperature of the pre-firing process ST2 is 1000°C. The heating temperature of the sintering process ST3 is 1370°C. The heating time in the sintering process ST3 is 20 seconds.
[0117] from Figure 15The diffraction pattern of the inorganic long fiber 15 shown in the reference example yields an average grain size of Dhkl = 25 (nm). That is, the average grain size of the mullite crystals in the inorganic long fiber 15 of the reference example is 25 nm. Here, the flexural strength of the grinding rod 10 of the reference example is 1200 MPa, and the flexural modulus is 116 GPa. In manufacturing the grinding rod 10 of the reference example, the heating temperature of the pre-firing process ST2 is 1000°C. The heating temperature of the sintering process ST3 is 1385°C. The heating time in the sintering process ST3 is 20 seconds.
[0118] from Figure 16 The diffraction pattern of Comparative Example 2 shows that the average grain size of the mullite crystals of the inorganic long fiber 15 is Dhkl = 30 (nm). That is, the average grain size of the mullite crystals of the inorganic long fiber 15 in Comparative Example 2 is 30 nm. Here, the flexural strength of the grinding rod 10 of Comparative Example 2 is 1200 MPa, and the flexural modulus is 117 GPa. In manufacturing the grinding rod 10 of Comparative Example 2, the heating temperature of the pre-firing process ST2 is 1000°C. The heating temperature of the sintering process ST3 is 1390°C. The heating time in the sintering process ST3 is 20 seconds.
[0119] (Comparative Test)
[0120] Using the whetstone 10 of Example 2, the whetstone 10 of the Reference Example, and the whetstone 10 of Comparative Example 2, the same comparative test as the above comparative test was conducted. Figure 17 It is the roughness curve of the grinding surface of the workpiece after grinding with the grinding stone rod 10 of Example 2. Figure 18 It is the surface roughness curve of the workpiece after grinding with the grinding stone 10 of the reference example. Figure 19 This is the surface roughness curve of the workpiece after grinding using the grinding stone 10 of Comparative Example 2. Figure 17 , Figure 18 , Figure 19 In the diagram, the horizontal axis represents the measured length (mm), and the vertical axis represents the height (μm).
[0121] Figure 20 This is a graph showing the grinding amount of the workpieces after a comparative test in which workpieces were ground using the grinding stone 10 of Example 2, the grinding stone 10 of the reference example, and the grinding stone 10 of the comparative example, respectively. Figure 20 In the middle, it is shown together Figure 12 The grinding amount of the grinding stone rod 10 in Example 1 and the grinding amount of the grinding stone rod 10 in Comparative Example 1 are shown. Figure 21 This is a graph showing the wear amount of the grinding stone 10 after a comparative test in which workpieces were ground using the grinding stone 10 of Example 2, the grinding stone 10 of the reference example, and the grinding stone 10 of the comparative example. Figure 21 In the middle, it is shown together Figure 13 The wear amount of the grinding stone rod 10 in Example 1 and the wear amount of the grinding stone rod 10 in Comparative Example 1 are shown.
[0122] from Figure 20 As shown in the graph of grinding amounts after the comparative tests, the grinding stone 10 of Example 1 (Dhkl = 20 nm), the grinding stone 10 of Example 2 (Dhkl = 10 nm), and the grinding stone 10 of the Reference Example (Dhkl = 25 nm) all have the same grinding force as the grinding stone 10 of Comparative Example 1 (Dhkl = 35 nm) and the grinding stone 10 of Comparative Example 2 (Dhkl = 30 nm). Specifically, the grinding amount of the grinding stone 10 of Example 1 is 0.110 g. The grinding amount of the grinding stone 10 of Example 2 is 0.109 g. The grinding amount of the grinding stone 10 of the Reference Example is 0.111 g. The grinding amount of the grinding stone 10 of Comparative Example 2 is 0.111 g.
[0123] In addition, from Figure 21 The graph showing the wear amount of the grinding stone rod 10 after the comparative test indicates that the wear amount of the grinding stone rod 10 in Example 1 (Dhkl = 20 nm), the wear amount of the grinding stone rod 10 in Example 2 (Dhkl = 10 nm), and the wear amount of the grinding stone rod 10 in the Reference Example (Dhkl = 25 nm) are less than the wear amount of the grinding stone rod 10 in Comparative Example 1 (Dhkl = 35 nm) and the wear amount of the grinding stone rod 10 in Comparative Example 2 (Dhkl = 30 nm). Specifically, the wear amount of the grinding stone rod 10 in Example 1 is 0.0029 g. The wear amount of the grinding stone rod 10 in Example 2 is 0.0028 g. The wear amount of the grinding stone rod 10 in the Reference Example is 0.0029 g. The wear amount of the grinding stone rod 10 in Comparative Example 1 is 0.0046 g. The wear amount of the grinding stone 10 in Comparative Example 2 was 0.0031g. Here, the wear amount of the grinding stone 10 in Examples 1, 2 and the Reference Example is less than 0.003g, which is more than 35% lower than the wear amount of the grinding stone 1 in Comparative Example 1.
[0124] Furthermore, through experiments conducted by the inventors, it was confirmed that in the crystal structure of the inorganic long fiber 15 of the grinding rod 10, the smaller the average grain size of the mullite crystals, the less wear occurs in the grinding rod 10. That is, when the grain size of the mullite crystals is less than 10 nm, and the peak value of the diffraction lines on the (210) plane of the mullite is buried by other diffraction lines, making it impossible to obtain the correct grain size, the wear of the grinding rod 10 is lower than that of the grinding rod 10 in Example 2. Therefore, the smaller the average grain size of the mullite crystals in the crystal structure of the inorganic long fiber 15, the higher the wear resistance of the grinding rod 10.
[0125] Next, based on the roughness curve of the grinding surface of the workpiece after grinding with the grinding stone rod 10 (Dhkl = 10 (nm)) of Example 2, Figure 17 The surface roughness of the grinding surface S of workpiece W, calculated to be Rz 2.04 μm, is further shown. Additionally, the roughness curve of the grinding surface of the workpiece after grinding with the reference grinding stone 10 (Dhkl = 25 nm) is also shown. Figure 18 The surface roughness of the workpiece W's grinding surface S, calculated to be Rz 2.06 μm, is based on the roughness curve of the workpiece's grinding surface after grinding with the grinding stone 10 (Dhkl = 20 (nm)) of Example 1. Figure 10 The calculated surface roughness of the grinding surface S of the workpiece W is Rz2.05μm. This value is between the surface roughness value of the workpiece after grinding with the grinding stone 10 of Example 2 and the surface roughness value of the workpiece after grinding with the grinding stone 10 of the Reference Example.
[0126] Furthermore, based on the surface roughness curve of the workpiece after grinding with the grinding stone 10 (Dhkl = 30 (nm)) of Comparative Example 2, Figure 17 The surface roughness of the grinding surface S of the workpiece W was calculated to be Rz 2.17 μm. Furthermore, based on the roughness curve of the grinding surface of the workpiece after grinding with the grinding stone 10 (Dhkl = 35 (nm)) of Comparative Example 1... Figure 11 The calculated surface roughness of the grinding surface S of workpiece W is Rz 4.13 μm. Therefore, the smaller the average grain size of the mullite crystal particles of inorganic long fiber 15, the better it can suppress the generation of scratches, and the smaller the surface roughness of the grinding surface S of workpiece W will be.
[0127] (Effects)
[0128] As confirmed by the above comparative tests, in the grinding rod 10, even if the average grain size of the mullite crystals in the crystal structure of the inorganic long fiber 15 is less than 25 nm, the same grinding force as that in the case where the average grain size of the mullite crystals is greater than 25 nm can be obtained.
[0129] Furthermore, in the crystal structure of the inorganic long fibers 15 of the grinding rod 10, if the average grain size of the mullite crystals becomes smaller, the generation of scratches and other defects is suppressed, and the surface roughness of the grinding surface S of the workpiece W after grinding decreases. Therefore, if a grinding rod 10 with an average grain size of mullite crystals of less than 25 nm in the crystal structure of the inorganic long fibers 15 is used, the surface roughness of the grinding surface S of the workpiece W after grinding can be reduced compared to cases where the average grain size of the mullite crystals is greater than 25 nm.
[0130] Furthermore, compared to cases where the average particle size of mullite crystals in the crystal structure of inorganic long fibers 15 is greater than 25 nm, the wear resistance of grinding rod 10 is improved.
[0131] Furthermore, if the average grain size of the mullite crystals in the crystal structure of the inorganic long fiber 15 is less than 20 nm, the surface roughness of the grinding surface S of the workpiece W after grinding can be reduced compared to cases where the average grain size of the mullite crystals exceeds 20 nm. Moreover, if the average grain size of the mullite crystals in the crystal structure of the inorganic long fiber 15 is less than 20 nm, the wear resistance of the grinding rod 10 is further improved compared to cases where the average grain size of the mullite crystals exceeds 20 nm.
Claims
1. A grinding stone rod, which is a rod-shaped grinding stone rod whose front end is pressed against the grinding surface of a workpiece to grind the grinding surface, wherein, The grinding stone rod has multiple inorganic long fibers extending along its axial direction and resin impregnated and cured in the inorganic long fibers. The cross-section of the inorganic long fibers is exposed at the front end, and it has elasticity to bend in a direction intersecting the axial direction. The inorganic long fibers contain 80-90% by weight of alumina and 20-10% by weight of silicon dioxide. The inorganic long fiber has a crystal structure consisting of mullite crystals and intermediate alumina. The average grain size of the mullite crystals is less than 25 nm. The peak value of the diffraction line of the (110) plane of mullite appears in the diffraction pattern obtained by irradiating the inorganic long fiber with X-rays. The average grain size of the mullite crystals was calculated based on the diffraction pattern using the following mathematical formula. 【Mathematical Formula 1】 D hkl (210) Average particle size of the surface, λ: the wavelength of X-rays θ: Grazing angle of X-rays β 1 / 2 The half-width of the diffraction line of the (210) plane of mullite, which appears near 26° based on the crystal structure 2θ of X-ray diffraction.
2. The grinding stone rod as described in claim 1, characterized in that, The average grain size of the mullite crystals is less than 20 nm.
3. The grinding stone rod as described in claim 1, characterized in that, The inorganic long fibers contain more than 85% alumina.
4. The grinding stone rod as described in claim 1, characterized in that, The resin is epoxy resin.
5. The grinding stone rod as described in claim 1, characterized in that, The flexural strength is above 500 MPa and the flexural modulus of elasticity is above 50 GPa.
6. A grinding method, characterized in that, The grinding stone rod of claim 1 is mounted on a vibrating tool, and the front end of the grinding stone rod is pressed against the grinding surface of the workpiece while vibrating it along the axial direction.
7. A grinding method, characterized in that, The grinding stone rod of claim 1 is mounted on a vibrating tool, and the front end of the grinding stone rod is pressed against the grinding surface of the workpiece while vibrating it along the axial direction and in the direction intersecting with the axial direction of the grinding stone rod.
8. A grinding method, characterized in that, The grinding stone rod as described in claim 1 is mounted on a rotating tool, and the front end of the grinding stone rod rotates while being pressed against the grinding surface of the workpiece. The cross-section of the grinding stone rod is circular.
Citation Information
Patent Citations
Ceramic fiber for processed material, its production and processed material containing the same
JP1998183427A
Alumina fiber and alumina fiber aggregate
WO2014115814A1
